2020
DOI: 10.17796/1053-4625-44.5.11
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective CBCT Study of the Relationship between Mandibular Symphysis Bone Density and Mandibular Growth Direction

Abstract: Objective: The objective of this retrospective study was to investigate the relationship between mandibular symphysis bone density (BD) and mandibular growth direction in adolescent patients by facilitating the measurement of cortical and cancellous BDs at the mandibular symphysis using cone beam computed tomography (CBCT). Study Design: 224 adolescent patients (98 males and 126 females) were categorized by sex, age, and mandibular growth direction. Cortical and cancellous BDs were measured along with a sagitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This BD result was verified by Mense et al 16 and Park et al, 32 who reported the cortical density range of the mandible in the alveolar bone as being around 700 to 1500 HU. Chae et al 33 in 2020, also revealed close values when they examined the BD of mandibular symphysis among young people (10–20 years old) of both gender. This suggests that bone density is preserved with age and after the loss of teeth.…”
Section: Discussionmentioning
confidence: 82%
“…This BD result was verified by Mense et al 16 and Park et al, 32 who reported the cortical density range of the mandible in the alveolar bone as being around 700 to 1500 HU. Chae et al 33 in 2020, also revealed close values when they examined the BD of mandibular symphysis among young people (10–20 years old) of both gender. This suggests that bone density is preserved with age and after the loss of teeth.…”
Section: Discussionmentioning
confidence: 82%
“…Meanwhile for the posterior growth direction with a hyperdivergent facial pattern, it has a long symphysis height, small width, large ratio, small symphysial angle, and narrow chin 16 . Mandibular growth can help diagnose orthodontics and treatment plans such as treatment duration, tool selection, extraction sequence and extraction needs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Язикова кортикальна пластинка зазвичай товща щічної. Кістка в ділянці верхівок зубів та язичної поверхні зазвичай товща у людей з широким і коротким симфізом [6], крім того, у жінок ища щільність кортикальної кістки в ділянці нижньощелепного симфізу, ніж у чоловіків [3].…”
Section: результати обговоренняunclassified